Modulation of endothelial factors activity in human endothelial cells in influenza A(H1N1)pdm09 virus infection - V. A. Marchenko; S. V. Barashkova; I. A. Zelinskaya; Ya. G. Toropova; E. S. Ramsay; I. N. Zhilinskaya (Вопросы вирусологии, 2021)
Introduction. Influenza A virus infection can lead to endothelial dysfunction (ED), including apoptosis of endothelial cells and modulation of endothelial factor activities. Affected biochemical factors may include those playing important roles in vascular homeostasis. However, the effect of this pathogen on the expression pattern of key endothelial factors is still unknown.